Influence of Mesenchymal Stem Cell Administration on The Outcome of Partial Liver Resection in a Porcine Model of Sinusoidal Obstruction Syndrome - Palek, Richard; Rosendorf, Jachym; Maleckova, Anna; Vistejnova, Lucie; Bajcurova, Kristyna; Mirka, Hynek; Tegl, Vaclav; Brzon, Ondrej; Kumar, Arvind; Bednar, Lukas; Tonar, Zbynek; Hosek, Petr; et al. (Anticancer research, 2020)
BACKGROUND: In patients with colorectal liver metastases, the possibility for radical liver resection can be limited by oxaliplatin-induced sinusoidal obstruction syndrome (SOS). This study investigates the potential of mesenchymal stem cells (MSC) to improve the outcome of liver resections in pigs with SOS. MATERIALS AND METHODS: SOS was induced in all animals (n=20) on day 0. Animals in the experimental group (n=8) received allogeneic MSC on day 7. Liver resection was performed in all animals on day 14 and the animals were observed until day 28. Ultrasound volumetry, biochemical analysis and histological examination of liver parenchyma was performed during the follow-up period. RESULTS: Six animals from the control group died prematurely, while all animals survived in the experimental group. According to histology, biochemical analysis and ultrasound volumetry, there were no significant differences between the groups documenting the effect of MSC. CONCLUSION: Single dose allogeneic MSC administration improved survival of animals with SOS undergoing partial liver resection. Further experiments with different timing of liver resection and MSC administration should be performed to investigate the effect of MSC in more detail.
Keywords: Male; zvířata; Immunophenotyping; imunofenotypizace; modely nemocí na zvířatech; kolorektální nádory; mezenchymální kmenové buňky; Swine; Combined Modality Therapy; výsledek terapie; prasata; Hepatic Veno-Occlusive Disease; Animals; Immunohistochemistry; jaterní žilní okluze; ženské pohlaví; Colorectal Neoplasms; Mesenchymal Stem Cell Transplantation; Treatment Outcome; hepatektomie; nádory jater; Disease Models, Animal; Mesenchymal Stem Cells; transplantace mezenchymálních kmenových buněk; Biomarkers; biologické markery; Hepatectomy; Female; mužské pohlaví; imunohistochemie; Liver Neoplasms; kombinovaná terapie